Access to justice and legal empowerment making the poor central in legal development co-operation - Meene, Ineke van de. (Law, governance, and development. Research & policy notes., 2008)
This volume answers a number of basic questions about this new trend in legal development cooperation: reforms to improve poor people's access to justice and to promote their legal empowerment.